Authority Of A Notary To Issue A Deed - Udin Narsudin (Sean Institute, 2025)
In order to determine heirs to ensure legal certainty, a Notary is the only party authorized to issue birth certificates for all Indonesian citizens regardless of their ethnic origin. This is based on the UUJN (Notary Position Law) which stipulates that a notary has the authority to determine evidence in the form of general letters, including a statement of heirs. A Notary is appointed by law as the sole owner or institution that has the right to issue Notaries for all Indonesians, as referred to in Article 15 paragraph. (1) UUJN, based on the authority of a Notary to determine the actual deed. The authority of a Notary is a personal authority and its own function must have legal meaning, be binding, so that its function can run well and not conflict with the authority of other functions. The issuance of inheritance deeds by a notary to all Indonesian citizens without discrimination is in accordance with the principles of law and upholds the law on safety and equality before the law. Likewise, the right of a Notary to provide evidence as an heir or as a statement of heirs is protected by the UUJN, a step that is in line with the concept of development law.